Business process model optimization using the conjugate gradient method - Kopp, A. M.; Orlovskyi, D. L. (Одеська національна академія харчових технологій, 2019)
This paper describes a model and a procedure of business process model optimization using the nonlinear conjugate gradient method. The research is based on business process modeling rules for BPMN (Business Process Model and Notation) as the de-facto standard for business process diagrams. Essential errors of business process modeling are outlined, as well as the metric used to define these shortcomings is denoted. Obtained results of business process model optimization are demonstrated.